A fuzzy expert system for career match based on personality / Noor Shuhada Abdullah - Abdullah, Noor Shuhada (Faculty of Computer and Mathematical Sciences, 2007)
As we seen nowadays, many graduates will be working in a field that different from what they have learned in university. This situation occurs because, they never has planning for their future career. This paper presents the development and implementation of fuzzy expert system for career match based on personality. The system's main objective is to perform personality traits in assisting the user to select the best match career. It is particularly usefiil for secondary students who intent to further their study in university where it could be as their guidance to select the best program to go for their best match career. There are six types of personality type such as realistic, investigative, artistic, social, enterprising and conventional and each group will provide the career that suit with the personality type. The process of matching the personality type with the career is performed through a fuzzy inference system. The system output is a measure of personality type suitability for the certain job. This fiizzy expert system can be used as a decision support tool for those who want to plan for their future career.